Post Reduction Mammaplasty Pyoderma Gangrenosum: An Unusual Presentation of a Misdiagnosed Entity (2020)
ABSTRACT: Pyoderma gangrenosum is a rare skin disorder that could be triggered after surgical trauma. However, more uncommon, this condition could follow breast surgery. An opportune diagnosis and adequate treatment are essential in order to avoid wound chronicity and aesthetic sequels. We report a 51-year-old woman who presented multiple wound complications after a reduction mammaplasty. This particular case is unique, because bilateral and unusual presentation after another uncomplicated previous surgical procedure, and illustrates how a patient could be taken through different rational surgical therapeutic modalities without improvement, and deterioration of clinical picture. Finally, a diagnosis of Pyoderma gangrenosum was established, and immunosuppressive treatment was completed, with an appropriate resolution of this problematic condition.